Pengaruh Trend Fashion, Social Media Marketing Dan Customer Experience Terhadap Keputusan Pembelian Pada Produk H&M (Studi Pada Mahasiswa Universitas Islam Malang 2021) - Aprilia, Rochimatul Ammar; Wahono, Budi; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstrack The purpose of this research is to determine and test the partial and simultaneous influence of Fashion Trends, Social Media Marketing, and customer experience on purchasing decisions for H&M products. The class of 2021 students at the Islamic University of Malang are the population for this research, with a total of 2,201 students. This research was assisted by the SPSS (Statistical Package for Social Science) computer program. Purchase Decisions are simultaneously influenced by Fashion Trends, Social media marketing and customer experience. Fashion trends, social media marketing, and customer experience partially have a positive and significant influence on purchasing decisions. Keywords : Trend Fashion, Social Media Marketing, Customer Experience, and Buying Decision.